1994
DOI: 10.1002/apmc.1994.052170112
|View full text |Cite
|
Sign up to set email alerts
|

Study of the mechanism of the antioxidant action of ethoxyquin

Abstract: ZUSAMMENFASSUNG:Die Reaktion von 6-Ethoxy-2,2,4-trimethyl-1 ,2-dihydrochinolin (Ethoxyquin, I) mit Alkylperoxyradikalen wurde untersucht. In Gegenwart einer relativ niedrigen Konzentration von 1 -Cyano-1 -methylethylperoxyradikalen reagiert I zu dem dimeren Hauptprodukt 8-(6-Ethoxy-2,2,4-trimethyl-1,2-dihydrochinolin-1 -yl)-6-ethoxy-2,2,4-trime-CCC 0003-3146/94/$05.00

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Ethoxyquin acts primarily as a hydrogen atom donor toward peroxyl radicals. The major oxidation products of ethoxyquin result from heterodimerization (compound 2 ) or loss of methyl (quinoline 3 ) or ethyl (quinoline quinone imine 4 ) radicals from the corresponding aminyl radical. The hyperfine splittings recorded in the EPR spectrum of the aminyl radical are indicative of extensive delocalization of the unpaired electron …”
Section: Introductionmentioning
confidence: 99%
“…Ethoxyquin acts primarily as a hydrogen atom donor toward peroxyl radicals. The major oxidation products of ethoxyquin result from heterodimerization (compound 2 ) or loss of methyl (quinoline 3 ) or ethyl (quinoline quinone imine 4 ) radicals from the corresponding aminyl radical. The hyperfine splittings recorded in the EPR spectrum of the aminyl radical are indicative of extensive delocalization of the unpaired electron …”
Section: Introductionmentioning
confidence: 99%
“…It was reported that PBN inhibits both synthesis of nitric oxide (NO) and formation of NO-mediated 3-nitrotyrosine adducts in activated astrocytes. Quinoline compounds have numerous biological applications such as anti-malarial [14], anti-microbial [15], anti-inflammatory [16], anti-cancer [17], anti-ulcer [18], antioxidant [19], and antiviral [20] activities.…”
Section: Introductionmentioning
confidence: 99%
“…Animal feeds often utilize ethoxyquin as it is the most effective antioxidant . This exceptional effectiveness is contributed to the ability for the oxidization products of ethoxyquin to also contain antioxidant properties (Taimr, 1994). Furthermore, the half-life of these products, such as ethoxyquin dimer, are considerably longer than ethoxyquin .…”
Section: Antioxidantsmentioning
confidence: 99%